Layanan Bimbingan Pranikah untuk Meningkatkan Kesiapan Calon Pengantin - Aini, Nurul; Hotimah, Nur; Jalaluddin, Moh.; Rosita, Eva; Muzayin, Azis (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2024)
One of the contributing factors to divorce is the lack of mental preparedness in dealing with the complexity of marital issues that were not previously discussed by prospective spouses, coupled with inadequate preparation for marriage. This study aims to evaluate the effectiveness of premarital counseling and assess the readiness of prospective spouses after participating in such counseling. The research employs a qualitative descriptive method, focusing on text-based data analysis. Conducted at the Office of Religious Affairs (KUA) in Batumarmar with prospective spouses as subjects, data collection techniques include observation, interviews, and documentation, validated through triangulation. Findings indicate that premarital counseling at KUA Batumarmar is crucial in preparing prospective spouses for marital life. They demonstrate mature mental readiness for marriage, a strong understanding of religious values, mutual support commitment, and social and financial preparedness for a sustainable and happy family life.